Between Normative and Empirical: The Establishment of Indonesia's Natural Resource Law (Legal System Perspective: Legal Substance) (Law Research Review Quarterly, 2015)
Lawrence M Friedman ordained the legal system covering aspects of substance, aspects of structure, and aspects of culture. These three aspects become a synergizing force in strengthening the implementation of a country's legal system in law formation. In the context of the formation of legislation often on the aspect of substance neglected because the theory of the operation of law in the community of William C. Chamblis and Robert B. Seidman is not running optimally. This is influenced by the political configuration chosen in the formation of legislation. Keywords: Normative, Empirical, Legal System, Natural Resources